HUBUNGAN USIA DAN PERSEPSI KERENTANAN DENGAN PERILAKU PROTEKSI PENULARAN TB PADA ANAK DI LIMA WILAYAH KERJA PUSKESMAS KOTA SEMARANG - Bonita, Bonita; Cahyo, Kusyogo; Riyanti, Emmy (Fakultas Kesehatan Masyarakat, 2018)
ABSTRACTThe number of TB cases in Semarang City was increased from 1.054 cases in 2014 tp 1.113 cases in 2015. Semarang is one of the cities with the highest TB cases in children in Central Java. The proportion of TB cases in children in Semarang City in 2016 amounted to 16%. This figure indicates that TB cases in children in Semarang City is exceeds the predetermined maximum limit of 13%. The main risk factor of tuberculosis in children due to close contact between children with smear positive TB patients. This study aims to analyze the behavior of TB patients in protecting TB transmission in children.This research is a quantitative research with cross sectional approach. The sample was chosen using proporsive sampling technique that is equal to 37 TB patients. The data were collected through interviews using questionnaires. Data analysis was done univariate and bivariate.The majority of respondents were of productive age (64.9%). The result of bivariate analysis shows that there is a significant correlation between perception of susceptibility (p = 0,033) with behavioral protection of TB transmission in children. While the age variables (p = 0.953) did not have a significant correlation with behavioral protection of TB transmission in children.